2021
DOI: 10.3390/universe7120472
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-LAT Observation of PSR B1259-63 during Its 2021 Periastron Passage

Abstract: PSR B1259-63 is a γ-ray binary system, where the compact object is a pulsar. The system has an orbital period of 1236.7 days and shows peculiar γ-ray flares (in 100 MeV–300 GeV) after its periastron time. We analyzed the Fermi-LAT observation of PSR B1259-63 during its latest periastron passage, as well as its previous three periastrons. The bright GeV flares started about 60 days after the periastron epoch in 2021. This delay is larger than that around the 2017 periastron and much larger than earlier periastr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The authors argue that these features are consistent with the emission cone model in the case of a sparser and clumpier disk of the Be star. • "Fermi-LAT Observation of PSR B1259-63 during Its 2021 Periastron Passage", by Zhi Chang et al [5] In this paper, authors compare all available Fermi-LAT data covering several periastron passages of PSR B1259-63 and confirm that the delay of the GeV flare in 2021 is larger than it was during the 2017 periastron and much larger than during earlier periastrons.…”
mentioning
confidence: 58%
“…The authors argue that these features are consistent with the emission cone model in the case of a sparser and clumpier disk of the Be star. • "Fermi-LAT Observation of PSR B1259-63 during Its 2021 Periastron Passage", by Zhi Chang et al [5] In this paper, authors compare all available Fermi-LAT data covering several periastron passages of PSR B1259-63 and confirm that the delay of the GeV flare in 2021 is larger than it was during the 2017 periastron and much larger than during earlier periastrons.…”
mentioning
confidence: 58%
“…It is still unclear exactly how (or even if) the differences in the X-ray and GeV lightcurves are correlated with the properties of the X-ray emitting clump (e.g., brightness, size). The X-ray and GeV lightcurves of the 2021 periastron passage showed some unique features, such as a third peak in the X-ray lightcurve and the most delayed, but intense, GeV emission observed yet from the binary (Chang et al 2021;Chernyakova et al 2021;Johnson et al 2021). Since another X-ray emitting clump has been detected after the 2021 periastron passage (Hare et al 2023), monitoring its size and brightness as it travels away from the binary will provide yet another opportunity to shed light on this fascinating phenomenon and system.…”
Section: Discussionmentioning
confidence: 96%
“…The lightcurve of B1259 typically shows two X-ray peaks attributed to the pulsar's passages through the Be star's decretion disk (Chernyakova et al 2014(Chernyakova et al , 2015. Fermi-LAT observations have shown that there are also GeV flares, seen only after periastron passages, with different delays and peak luminosities in different binary cycles (see, e.g., Johnson et al 2018;Chang et al 2021;Chernyakova et al 2021). The X-ray emission during the 2017 periastron passage showed a delayed X-ray peak occurring ∼5-10 days after the pulsar crossed the decretion disk for the second time and a GeV flare that was more delayed (∼60 days after periastron in 2017 versus ∼30 days in 2014 and 2010) and had higher peak luminosities, some of which exceeded the spin-down luminosity of the pulsar (Chang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the known gamma-ray binaries, PSR B1259 −63 is known to flare once per 3.4-yr orbit (e.g. Abdo et al 2011 ;Tam et al 2011Tam et al , 2018Caliandro et al 2015 ;Chang et al 2021 ). Ho we ver, this binary is far less compact than others, with d ∼ 0 .…”
Section: Connection To This Workmentioning
confidence: 99%